Sonic Heritage and Acoustic Profiling of the Gendang Kecapi: A Bamboo-Based Instrument from Kelantan, Malaysia - Aaliyawani Ezzerin, Sinin; Sinin, Hamdan; Khairul Anwar, Mohd Said; Muhamad Zuhairi, Sulaiman; Mawar Suhaila, Ab Razak; Ahmad Faudzi, Musib (North Carolina State University (NCSU), 2025)
This study considered the ‘Gendang Kecapi’ (GK) musical instrument, the sounds of which were recorded in an anechoic chamber. The Fast Fourier Transform (FFT) data was obtained using a Picoscope oscilloscope. The GK is an idiochord bamboo tube zither from Kelantan, Malaysia. The GK have two strings (called canang), two gongs,and a gendang(drum). The instrument produced unique and innovative sounds. The time frequency analysis (TFA) used Adobe Audition to produce the spectrograms. The fundamental frequency (f0) of string 1 (canang ibu) and string 2 (canang anak) are 0.888 kHz (A5) and 1.054 kHz (C6), respectively. The f0 of gong 1 (gong ibu) and gong 2 (gong anak) are0.230 kHz (A3#) and 0.246 kHz (B3),respectively. The f0 of gendang is 0.380 kHz (F4#). The frequency spectrum showed less distinct fundamental frequency with several lower partial frequencies at 0.017, 0.100, and 0.200 kHz